(3GddOGFf(B-(3GdHdGSJjc GdMQGQj (B/s - (3NdjaI, SdjeGfs ((3OeTb (B:s (3OGQ OeTb ddWHGYI hGdfTQ hGdJhRjY,s, 1996)
(3eONd Edi Yde GdHdGSJjc(B-(3GdHdGSJjc GdMQGQj(B-(3GdCSjJGdGJ(B-(3GdCcQjdjc(B-(3GdSdjhdhRGJ(B-(3GdfGjdhf(B-(3GdHhdj cQHhfGJ(B-(3GdHhdjeQGJ GdMQGQjI(B-(3GdHhdj EKjdjf(B-(3GdHhdj EjejOGJ GdMQGQjI(B-(3ehGO HdGSJjcjI ebGheI ddgH hGdcjeGhjGJ(B-(3GdadhQhcQHhfGJ(B-(3GdcjJhfGJ(B-(3GdfJQjdGJ(B-(3ehGO HdGSJjcjI HWjFI GdGMJQGb(B-(3GdHhdj HQhHdjfGJ(B-(3GdQjRjfGJ GdSJjQjfjI(B-(3GdQjRjfGJ PGJ GdCSGS GdShdahfj(B-(3GdEjdGSJhejQGJ GdMQGQjI(B-(3GdQjRjfGJ PGJ GdCSGS ajfjd(B-(3GdehGO GdHdGSJjcjI GddaMjI hGdebGheI ddMQGQI(B-(3GdHhdj cMhdGJ(B-(3GdfTGA(B.s
Keywords: (3UfGYI hJLGQI GdHdGSJjcs; (3GdHdGSJjc GdMQGQjs; (3GdHdGSJjcs -- (3VHW LhOIs; (3GdHdGSJjc(B.s